Experimental and modelling studies of microwave plasma afterglows in N2–O2 mixtures. (23rd June 2015) - Annušová, A; Foissac, C; Veis, P; Supiot, P
Abstract: This paper presents results from both experimental and modelling studies of a flowing afterglow in N2 –O2 mixtures observed in a plasma-chemical reactor. The plasma is generated at a pressure of 440 Pa by a microwave cavity working at the excitation frequency of 433 MHz. The main nitrogen and nitrogen oxide species are experimentally studied, mainly in the late afterglow of both a N2 –O2 discharge and a nitrogen discharge with a downstream O2 admixture. The molecules and relative densities were monitored by optical emission spectroscopy and the atoms by means of mass spectrometry. A temporal 0D model is built and coupled to a steady state model on and states, for comparison with the experimental results, in order to describe the kinetics of the studied afterglows. This calculation is supported by the simulation of gas flow in the reactor using COMSOL Multiphysics ® . We present results concerning the temporal density evolutions of, , , , , and steady density evolutions of and species as functions of the amount and location of an oxygen injection. The principal mechanisms in the described system are identified allowing the proposal of a simplified kinetic scheme showing a strong coupling among, and the main channels of the formation and destruction of NO, NO2 and O3 molecules.